PENGARUH LITERASI KEUANGAN, DIGITAL PAYMENT DAN KEMAMPUAN MENYUSUN LAPORAN KEUANGAN TERHADAP KINERJA UMKM - Zidni Husnia Fachrunnisa; Nugraeni Putrie Windarti; Ratna Purnama Sari (JURNAL FAIRNESS, 2024)
MSMEs can drive the country's economic growth, however, the performance of MSMEs has experienced a slowdown due to the Covid 19 pandemic. So, this research aims to find out what factors can encourage the performance of MSMEs. This research uses internal and external organizational factors that can influence MSME performance, such as financial literacy, digital payment, and the ability to prepare financial reports. The population of this research is MSMEs in Bantul Regency. The sampling method uses a purposive sampling technique with the criteria of MSMEs that have used digital payments and financial records. The samples that can be used are 108 MSMEs in Bantul Regency. Data collection was carried out using a questionnaire method which was distributed offline by visiting MSMEs and online using Google from. Data processing uses the SPSS Statistics 26.0 application. Data were analyzed using multiple linear regression analysis. The research results show that financial literacy and the use of digital payments have no effect on MSME performance, while the ability to prepare financial reports has a positive effect on MSME performance. High or low levels of financial literacy and the use of digital payments do not affect the performance of MSMEs. Meanwhile, the higher the ability to prepare financial reports, the higher the performance of MSMEs will be. MSMEs that prepare financial reports can evaluate their business performance.